Zur Frage einer Teilnahme evangelischer und katholischer Christen an Abendmahlsfeiern der anderen Konfession - Wenz, Gunther (Zeitschrift für katholische Theologie, 2005)
This contribution takes a differentiated look at the problems of intercommunion of catholic and protestant christians. It does this with special reference to official church documents and shows ecclesiological interpretations to be at the root of the differences in the praxis of celebrating the Lord's supper.